2021
DOI: 10.1007/s40256-021-00490-w
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Use of Statins and Clinical Outcomes in Patients with COVID-19: A Systematic Review and Meta-analysis

Abstract: Purpose Previously, we have reported potential clinical benefits with the use of statins in patients with coronavirus disease 2019 (COVID-19) in a meta-analysis, where there was a significantly reduced hazard for a fatal or severe course of illness with the use of statins, but the meta-analysis was limited by the small number of studies included, with small heterogeneity among studies, due to the unavailability of more studies at the point of literature search. We aimed to perform an updated syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…With regards to controlling dyslipidemia, the most commonly used class of drugs is Statins and studies have been ambivalent. Some meta-analyses conclude better outcome from retrospective studies ( 189 ) whilst others report improvement, worsening or no effect ( 190 ).…”
Section: Covid-19 Severity and Type-2 Diabetesmentioning
confidence: 99%
“…With regards to controlling dyslipidemia, the most commonly used class of drugs is Statins and studies have been ambivalent. Some meta-analyses conclude better outcome from retrospective studies ( 189 ) whilst others report improvement, worsening or no effect ( 190 ).…”
Section: Covid-19 Severity and Type-2 Diabetesmentioning
confidence: 99%
“…A meta‐analysis of 13 observational studies found a 27% reduction in negative clinical outcomes, when adjusting for confounding variables, namely in‐hospital mortality or severe disease 14 . Another meta‐analysis confirmed the association of statin use with lower risk of all‐cause mortality and severe illness, but noted the limitations of sample size and heterogeneity between studies 15 . This suggests that further analysis and controlled trials are needed to better understand the potential of statins as a COVID‐19 treatment…”
Section: Discussionmentioning
confidence: 99%
“…14 Another meta-analysis confirmed the association of statin use with lower risk of all-cause mortality and severe illness, but noted the limitations of sample size and heterogeneity between studies. 15 This suggests that further analysis and controlled trials are needed to better understand the potential of statins as a COVID-19 treatment | 173…”
Section: Discussionmentioning
confidence: 99%
“…However, since statins are drugs prescribed for patients with cardiovascular complications that constitute predisposing factors for SARS-CoV-2 infection, the results from these observational studies are often controversial due to multiple confounding factors and clinical bias influencing data interpretation [ 39 ]. Despite this, the overall conclusion emerging so far from several meta-analyses is that statins used in COVID-19 patients is associated with improved clinical outcomes and reduced Intensive Care Unit (ICU) admission, mechanical intubation, ARDS, and in-hospital death [ 20 , 40 , 41 , 42 ]. The studies included in these meta-analyses and emerging observational studies [ 43 , 44 ] strongly suggest that statin therapy exerts a protective effect against complications from COVID-19, preventing the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%